(untitled) (Takwil: Journal of Quran and Hadith Studies, 2024)
This article aims to comprehensively reveal the method of Tafsir al-Maudu’iy in Al-Fatihah Verse. The article adheres to conventional academic structure and employs clear, objective, and value-neutral language. The object of this study is Karim Amsansaf’s Suratu al-Fatihah: Tafsir Maudu’iy fi Daui ‘Ibadati al-Du’ai, Muhammad ibn ‘Abd al-’Aziz al-’Awajiy’s al-Tafsir al-Maudu’iy al-Muyassar li al-Fatihah wa Qasari al-Mufassali, and the book titled Ila al Qur’an al-Karim, written by Muhammad al-Ghazali and Mahamud Shaltut, attempts to examine various legacies of tafsir works that are rarely researched by the public. An examination of the three tafsir shows differences in their interpretive products, with a focus on revealing in-depth thematic aspects on the intrinsic and extrinsic side, as stated by Muhammad ibn ‘Abd al-’Aziz al-’Awajiy. The text discusses the principles of thematic interpretation in Tafsir Maudu’iy, with a focus on the thematics expressed by Karim Amsansaf. The discussion is aimed at beginner readers or lay people and is presented in a simple manner. The text also mentions the use of the thematic tafsir method and its application to the interpretation of Al-Fatihah.